Removal of N-terminal tail changes the thermostability of the low-temperature-active exo-inulinase InuAGN25. Issue 1 (1st January 2020) - He, Limei; Zhang, Rui; Shen, Jidong; Miao, Ying; Tang, Xianghua; Wu, Qian; Zhou, Junpei; Huang, Zunxi
ABSTRACT: Exo-inulinases are members of the glycoside hydrolase family 32 and function by hydrolyzing inulin into fructose with yields up to 90–95%. The N-terminal tail contributes to enzyme thermotolerance, which plays an important role in enzyme applications. However, the role of N-terminal amino acid residues in the thermal performance and structural properties of exo-inulinases remains to be elucidated. In this study, three and six residues of the N-terminus starting from Gln23 of the exo-inulinase InuAGN25 were deleted and expressed in Escherichia coli . After digestion with human rhinovirus 3 C protease to remove the N-terminal amino acid fusion sequence that may affect the thermolability of enzymes, wild-type RfsMInuAGN25 and its mutants RfsMutNGln23Δ3 and RfsMutNGln23Δ6 were produced. Compared with RfsMInuAGN25, thermostability of RfsMutNGln23Δ3 was enhanced while that of RfsMutNGln23Δ6 was slightly reduced. Compared with the N-terminal structures of RfsMInuAGN25 and RfsMutNGln23Δ6, RfsMutNGln23Δ3 had a higher content of (1) the helix structure, (2) salt bridges (three of which were organized in a network), (3) cation–π interactions (one of which anchored the N-terminal tail). These structural properties may account for the improved thermostability of RfsMutNGln23Δ3. The study provides a better understanding of the N-terminus–function relationships that are useful for rational design of thermostability of exo-inulinases. Graphical Abstract: